Antilogic - Benoît Castelnérac; Mathieu Marion (Baltic International Yearbook of Cognition, Logic and Communication, 2013)
This paper is an interim report of joint work begun in (Castelnérac & Marion 2009) on dialectic from Parmenides to Aristotle. In the first part we present rules for dialectical games, understood as a specific form of antilogikê developed by philosophers, and explain some of the key concepts of these dialectical games in terms of ideas from game semantics. In the games we describe, for a thesis A asserted by the answerer, a questioner must elicit the answerer’s assent to further assertions B1, B2,…, Bn, which form a scoreboard from which the questioner seeks to infer an impossibility (adunaton); we explain why the questioner must not insert any of his own assertions in the scoreboard, as well as the crucial role the Law of Non Contradiction, and why the games end with the inference to an impossibility, as opposed to the assertion of ¬A. In the second part we introduce some specific characteristics of Eleatic Antilogic as a method of enquiry. When Antilogic is used as a method of inquiry, then one must play not only the game beginning with a given thesis A, but also the game for ¬A as well as for A & ¬A, while using a peculiar set of opposite predicates to generate the arguments. In our discussion we hark back to Parmenides’ Poem, and illustrate our points with Zeno’s arguments about divisibility, Gorgias’ ontological argument from his treatise On Not-Being, and the second part of Plato’s Parmenides. We also identify numerous links to Aristotle, and conclude with some speculative comments on the origin of logic.
Keywords: game semantics; dialectical games; Aristotle; origins of logic